The globalization of world politics an introduction to international relations (Oxford University Press, 2005)
Conclusion 000 "The Globalization of World Politics is the essential text for all International Relations students. With its established authority and reputation, the new edition is an invaluable resource, which provides a clear and insightful introduction to International Relations and acts as a comprehensive point of reference thereafter." "The third edition has been fully revised and updated in the light of recent developments in world politics, with new chapters on international law, terrorism, and social constructivism."